Normas tributárias e direitos sociais - Frederico Menezes Breyner (2017)
The main topic of this thesis is the use of tax law as a tool to promote social rights by means of tax expenditures associated to the state duty to facilitate access to social goods granted by those rights. Theories of justice that provide grounds to the guarantee and financial support of those rights, as well as principles of justice to guide the use of tax expenditures were analyzed. Before this theoretical background, the analysis was directed to the fundamental rights dogmatically, demonstrating the social rights as fundamental rights. The thesis proposes that these tax expenditures are qualified as rules assigned to fundamental social rights, characterized by its binding, priority, and unavailability, offering resistance against retrogressive measures. The tax expenditure analysis linked in a stronger way tax law and social rights by relating tax breaks and public expenditures. This relation made possible to increase the control over retrogressive measures by identifying legal principles that can justify retrogressive measures against social rights implemented by tax expenditures and arguments that cannot provide such justification. By way of the proportionality test to approach the interaction between principles that play for and against retrogressive measures, this thesis analyzed the criteria to assess its conformity with the Constitution, using as concrete examples the increase of indirect taxation over social goods and the abrogation of constitutional prohibitions of taxation that protects social rights.